Stacking optimization of 3D printed continuous fiber layer designs. (February 2022) - Opalach, Kamil; Porter-Sobieraj, Joanna; Zdroik, Przemysław
Highlights: Continuous fiber filament paths generation for 3D printing. Loadcase specific internal structure optimization for anisotropic materials. Automation of FEM simulation for finding optimal fiber orientation. Computer-aided composite part design for 3D printing with continuous fiber. Abstract: The use of composite materials in 3D printing, such as fiber-reinforced plastic, allows the created parts to achieve better mechanical properties. However, it requires a new approach to the design of the 3D printed parts, especially in the case of anisotropic materials with a continuous fiber filament. Different layer configurations, built using a different arrangement of continuous carbon fibers, result in varying properties of the printed part. This paper presents a novel multi-step incremental algorithm for finding the optimal sequence of layers for an object intended for 3D printing. The optimization criterion may be any scalar value describing a required property, e.g. the strength or stiffness of the part derived from simulation of the designed element using the finite element method. Detailed analysis of the proposed algorithm, and numerical results obtained for various load cases and different input data, proves that the proposed method significantly accelerates and facilitates the process of designing a part to meet given requirements. Thanks to the incremental approach, it also works efficiently in the case of sequences with a very large target number of layers and may be used in real-world engineering applications.